Varisonality and Surface Levels in Crystals with an Ionic Bond - Z. I. Karimov; B. L. Oksengendler; S. Kh. Suleymanov; A. S. Doroshkevich; A. F. Zatsepin; N. N. Nikiforova; N. A. Kulagina (Research Highlights in Science and Technology Vol. 1, 2023)
Based on the rethinking of the Seitz scheme (1940), a new concept of the electronic structure of interfaces (including the surface) of ionically bonded crystals is proposed in the article. It is shown that the Coulomb long-range action transforms an ordinary structure with Tamm levels into a group of local levels from the Airy problem. In the same vein, the electronic structure of the interface of a layered structure with a fractal layer (in the form of a Sierpinski carpet) was studied. The obtained results turned out to be very useful for solving a number of problems in nanoelectronics.